Global Value Chains and Trade Policy - Blanchard, Emily J; Bown, Chad P; Johnson, Robert C (Review of Economic Studies, 2026)
Abstract How do global value chain (GVC) linkages modify countries’ incentives to impose import protection? Are these linkages important determinants of trade policy in practice? We develop a new approach to modelling tariff setting with GVCs, in which optimal policy depends on the nationality of value-added content embedded in home and foreign final goods. Theory predicts that discretionary tariffs will be decreasing in the domestic content of foreign-produced final goods and the foreign content of domestically produced final goods. Using data for 14 countries between 1995 and 2015, we show that governments set lower tariffs and curb their use of temporary trade barriers where GVC linkages are strongest, consistent with theory. Turning to quantitative model counterfactuals, we find that severing GVC linkages would lead to the disappearance of tariff preferences. Further, targeted policies to decouple China from GVCs would increase the optimal tariff set by G7 countries on Chinese exports.